2020
DOI: 10.3389/fpsyt.2020.00716
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol, a SIRT1 Activator, Ameliorates MK-801-Induced Cognitive and Motor Impairments in a Neonatal Rat Model of Schizophrenia

Abstract: Background: In neonatal rats, MK-801 treatment generates schizophrenia-like symptoms. Resveratrol (RSV) is a phenolic compound and a potent neuroprotective agent. This research aimed to illustrate the effect of RSV on the amelioration of MK-801induced cognitive and motor impairments in a neonatal rat schizophrenia model and the related potential molecular changes. Methods: Rats were administrated with MK-801, MK-801 + RSV (40 mg/kg), or MK-801 + RSV (80 mg/kg). Motor learning, coordination, locomotor and explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Female animals were included in the MAM model along with the males as there are very few reports on MAM models of schizophrenia using female animals [45,46]. Although the doses of 0.5 mg/Kg and 1.0 mg/Kg of MK-801 were used previously in separate studies, our study involves detailed comparative analysis of behaviour upon administration of these doses [29][30][31][32][47][48][49]. In our treatment regime, the washout period of 5 days ensures that the drug per se won't interfere with the behavior and hence the observed behavioral changes could be arising from the drug-induced changes in the brain tissue (Figure 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female animals were included in the MAM model along with the males as there are very few reports on MAM models of schizophrenia using female animals [45,46]. Although the doses of 0.5 mg/Kg and 1.0 mg/Kg of MK-801 were used previously in separate studies, our study involves detailed comparative analysis of behaviour upon administration of these doses [29][30][31][32][47][48][49]. In our treatment regime, the washout period of 5 days ensures that the drug per se won't interfere with the behavior and hence the observed behavioral changes could be arising from the drug-induced changes in the brain tissue (Figure 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…MK-801 is a non-competitive NMDAR channel blocker. It was intraperitoneally administered in two different doses -0.5 mg/Kg and 1.0 mg/Kg for five days based on previous reports [30][31][32][33]. The resulting blockage of NMDAR is expected to cause alterations in the brain similar to schizophrenia.…”
Section: 41treatment Regimes For the Animal Modelsmentioning
confidence: 99%
“…PLSs may also have other accompanying symptoms, such as cognition impairment and emotional disorder (e.g., mania and depression) ( 7 , 8 ). Schizophrenia can occur at different stages of life course, while the risk varies across different age groups ( 9 ). Reports have shown that the prevalence of schizophrenia changes with age in an inverted U-shape, with the highest value at around 40 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Each mouse was tested for three trials with an interval of 30 min. The time spent on the rotating rod was used for evaluation of the motor coordination and balance 59 .…”
Section: Methodsmentioning
confidence: 99%